Effect of welding time on microstructure and mechanical properties of Al-Ti ultrasonic spot welds. (June 2018) - Zhou, L.; Min, J.; He, W.X.; Huang, Y.X.; Song, X.G.
Abstract: AA6061 A l alloy and commercial pure Ti sheets were successfully joined by ultrasonic spot welding. The microstructure and mechanical properties of joints under welding time from 0.6 s to 1.4 s were investigated. No intermetallic compounds were founded at the interface of the joints. As the welding time increased, the peak load of the joints firstly increased with the expansion of bond area, then decreased afterwards due to the fatigue crack in Al side. The peak temperature increased with increasing welding time. In the weld region, the aluminum alloy was softened by the weld energy, while the hardness of pure titanium did not change distinctly. All the failure occurred along the interface of the joints with brittle fracture characteristics during tensile shear test.